PENGARUH KEPEMIMPINAN KEPALA SEKOLAH, KINERJA GURU DAN PERAN WALI MURID TERHADAP KEDISIPLINAN SISWA DI SMP NEGERI 51 MERANGIN - Saragih, Hasmailena; Susanti, Evi; Ningsih, Retno Wahyu (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the contributions of principal leadership, teacher performance, and parents’ involvement to students’ discipline at SMP Negeri 51 Merangin. A qualitative approach with a case study design was employed. Data were collected through semi-structured in-depth interviews, observation, and documentation. Informants were selected purposively, involving the principal, vice principal for student affairs, guidance and counseling teacher, homeroom teachers, subject teachers, parent representatives, and student representatives. Data were analyzed interactively through data condensation, data display, and conclusion drawing/verification, while source and method triangulation were used to enhance trustworthiness. The findings indicate that students’ discipline is strengthened by consistent principal leadership through role modeling, supervision, and policy enforcement; by teacher performance through classroom management, educative firmness, and positive reinforcement; and by parents’ involvement through active communication, home supervision, and support for school rules. In addition, the synergy of school regulations, violation records, and follow-up interventions conducted by homeroom teachers and counseling services enhances the effectiveness of discipline initiatives. The study concludes that student discipline is more effectively developed when leadership, classroom practices, and family support are aligned within a structured disciplinary system.